2016
DOI: 10.1159/000443037
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and Systemic Effects of LASSBio596 Plus Surfactant in Experimental Acute Respiratory Distress Syndrome

Abstract: Background/Aims: Exogenous surfactant has been proposed as adjunctive therapy for acute respiratory distress syndrome (ARDS), but it is inactivated by different factors present in the alveolar space. We hypothesized that co-administration of LASSBio596, a molecule with significant anti-inflammatory properties, and exogenous surfactant could reduce lung inflammation, thus enabling the surfactant to reduce edema and improve lung function, in experimental ARDS. Methods: ARDS was induced by cecal ligation and punc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Development of pulmonary fibrosis has been reported as a severe side effect following thoracic radiotherapy to treat lung and breast cancer [59]. The association of respiratory distress syndrome (RDS) with the induction of pulmonary fibrosis has also been reported and even the approach to cure both RDS and fibrosis through treatment with single adjuvant was issued in current study [60, 61]. RDS is caused by loss of pulmonary surfactant and the deficiency of SP-B and SP-C was observed in acute and chronic RDS (ARDS and CRDS) patients [62].…”
Section: Discussionmentioning
confidence: 99%
“…Development of pulmonary fibrosis has been reported as a severe side effect following thoracic radiotherapy to treat lung and breast cancer [59]. The association of respiratory distress syndrome (RDS) with the induction of pulmonary fibrosis has also been reported and even the approach to cure both RDS and fibrosis through treatment with single adjuvant was issued in current study [60, 61]. RDS is caused by loss of pulmonary surfactant and the deficiency of SP-B and SP-C was observed in acute and chronic RDS (ARDS and CRDS) patients [62].…”
Section: Discussionmentioning
confidence: 99%
“…The pilot study demonstrated notable mortality rates in patients; however, those with increased mRNA expression of SP generally exhibited a decreased incidence of allograft rejection by the innate immune system, thus illustrating a marked difference in lung transplant mortality associated with surfactants. Additionally, Silva et al ( 24 ) observed that the application of the anti-inflammatory agent LASSBio596 may be applied to ARDS mouse models to increase survival rates by mitigating macrophages, neutrophils and transforming growth factor-β by increasing surfactant yield, which in turn reduced surface tension. By maintaining elasticity and surfactant alterations in lung mechanics, the authors were able to counteract degradation immediately following lung injury leading to ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Total leukocyte counts were measured in a Neubauer chamber under light microscopy after diluting the samples in Türk’s solution (Merck KGaA, Darmstadt, Germany). For differential cell counts (mononuclear cells and neutrophils), cytospin slides were prepared and stained by the panoptic method (Laborclin, Pinhais, PR, Brazil) [17].…”
Section: Methodsmentioning
confidence: 99%
“…The volume fractions of collapsed and normal pulmonary areas were determined by the point-counting technique at a magnification of ×200 across 10 random, noncoincident microscopic fields [17].…”
Section: Methodsmentioning
confidence: 99%